2015
DOI: 10.3390/antiox4020410
|View full text |Cite
|
Sign up to set email alerts
|

Study of Polyphenol Content and Antioxidant Capacity of Myrianthus Arboreus (Cecropiaceae) Root Bark Extracts

Abstract: In order to evaluate the therapeutic potential of polyphenolic extracts from root bark of M. arboreus, we have determined the content of various polyphenols in aqueous and ethanol (EtOH) extract as well as two sub-fractions of the latter: ethyl acetate (EAc) and hexane (Hex). The total phenols, flavonoids, hydroxycinnamic acids and proanthocyanidins have been determined for all studied extracts/fractions by spectrophotometric methods. Both TP content (331.5 ± 2.5 mg GAE/g) and HCA content (201 ± 1.5 mg CAE/g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 39 publications
6
58
0
1
Order By: Relevance
“…It is generally proven that the antioxidant activity of plants depends on the amounts of biologically active compounds (flavonoids, phenolics, phenylpropanoids, etc.). Generally, the higher the TPC and TFC, the stronger antioxidant and antifungal activities reported [16,18,26]. In the current study, the various solvent extracts of HFF were taken for analysis, where AE showed the higher antioxidant activity in DPPH radical-scavenging assay, and EAE exhibited the stronger antioxidant activities in ABTS radical-scavenging and the FRAP assay.…”
Section: In Vitro Antioxidant Activities Of Hff Extractsmentioning
confidence: 86%
“…It is generally proven that the antioxidant activity of plants depends on the amounts of biologically active compounds (flavonoids, phenolics, phenylpropanoids, etc.). Generally, the higher the TPC and TFC, the stronger antioxidant and antifungal activities reported [16,18,26]. In the current study, the various solvent extracts of HFF were taken for analysis, where AE showed the higher antioxidant activity in DPPH radical-scavenging assay, and EAE exhibited the stronger antioxidant activities in ABTS radical-scavenging and the FRAP assay.…”
Section: In Vitro Antioxidant Activities Of Hff Extractsmentioning
confidence: 86%
“…Natural antioxidants have been studied extensively since they can protect cells from such oxidative damage and are assumed to be less toxic than synthetic antioxidants, such as butylated hydroxyanisole (BHA) and butylated hydroxyltoluene (BHT). However, they have been reported to cause liver damage and cancer 8 . In the present study, three medicinal plants viz.…”
Section: Introductionmentioning
confidence: 99%
“…[51,52] 100 lM of DPPH in ethanol was prepared and mixed with GA, ECG, and EGCG such that the final concentration of the polyphenol is 100 lM with ascorbic acid as the control. The reaction mixture was then incubated in the dark for 30 min at room temperature.…”
Section: Antioxidant Activity By Dpph (22-diphenyl-1-picrylhydrazymentioning
confidence: 99%